IDENTIFYING AND MANAGING OBSTETRIC EMERGENCIES IN NON-OBSTETRIC SETUP - Dr Azmat Jahan Mantoo; Dr Umer Hamid; Meshram, Dr Aishwarya; Dr Saadat Raj Mantoo (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Acute abdominal pain in pregnancy poses a significant diagnostic challenge. The differential diagnosis is wide, clinical assessment is difficult, and the use of conventional imaging methods is restricted due to risks to the fetus. This can lead to delay in diagnosis, which increases the risk of maternal and fetal harm. To curb the morbidity and mortality associated with delayed/missed diagnosis, knowledge of the frequency, aetiologies, and clinical presentation of acute abdomen in pregnancy is needed to aid us to make prompt and accurate diagnoses. Objectives: To assess the aetiologies and review clinical profile of acute abdomen in pregnancy. Methods: It was an observational study done over a period of 1year which included all the pregnant women who presented with acute abdomen. Results: A total of 118 pregnant women presented with acute abdomen during our study. The mean age of the study participants was 28 years. Concerning gravidity, 27.11% of patients were primigravida (first pregnancy). Most patients (66.94%) were multi-gravida (2 - 4 pregnancies) and 0.05% were grand multi-gravida (5 or more pregnancies). Most cases (65.25%) of acute abdomen in pregnancy were observed during the first trimester of pregnancy. 28.81% and 5.94% occurred in the 2nd and 3rd.Gynaeco-Obstetrics aetiologies of acute abdomen in pregnancy comprise a vast majority (83.05%) of causes. Acute appendicitis (3.38%) is the commonest non-obstetric surgical aetiology of acute abdomen in pregnancy. The most consistent symptoms and signs were abdominal pain (100%) and abdominal tenderness (96.61%) respectively. 76.27% had per vaginal bleeding, 25% had nausea/vomiting, 23% had fever, and 18% presented with anorexia.16% of patients had signs of peritonism. Conclusion: Diagnosis and treatment of acute abdomen in pregnancy should be individualized. Good clinical acumen is essential for ordering early diagnostic test in acute abdomen in pregnancy. Appropriate intervention should be undertaken at the earliest to reduce the maternal and fetal complications.